USING POWER POINT PROGRAM IN IMPROVING STUDENTS’ VOCABULARY MASTERY - Euis Yanah Mulyanah (Universitas Muhammadiyah Tangerang, 2018)
AbstractThis research investigates to know whether the PowerPoint program applied in teaching vocabulary and how whether student’s vocabulary development at 12th grade of SMA Al-Husna Kota Tangerang in academic year 2014/2015. The writer collected the data from 40 students spread in two group, experimentaland controlledgroup by applying quasi experimental design. The populations arestudents of 12th Grade of SMA Al-Husna Kota Tangerang consists of 60 students, XII IPA and XII IPS. The data is gathered through pretest and posttest, the result of the research shows that the hypothesis, which states null hypothesis is rejected. It means that there is significant difference of teaching students’ vocabulary mastery both classes and teaching vocabulary by using PowerPoint program would be better and more effective than teaching students’ vocabulary without PowerPoint program at 12th grade of SMA Al-Husna Kota Tangerang in academic year 2014/2015. Keywords : PowerPoint Program, Vocabulary Mastery